EFEKTIVITAS LAYANAN INFORMASI MENGGUNAKAN PERMAINAN UNTUK MENINGKATKAN SELF REGULATED LEARNING - Utami, Rismar Julia (Menara Ilmu, 2018)
This research background is lack of student self regulated learning, it has negative effects forthe quality and quantity of learning. Guidance and counseling services have a duty and role inimproving students self regulated learning, one of them is information service. Students will begiven an understanding and knowledge to improve student self-regulated learning byinformation service.The research purpose to reveal the effectiveness of information services toimprove student self-regulated learning. This research using quantitative research methodwith quasi-experimental approach by using the non equivalent control group design. Theresearch population was 115 students XI class in SMA N 13 Kerinci and selected by purposivesampling technique. Student self regulated learning data was Likert Scale, then analyzed usingthe Wilcoxon Signed Ranks Test and Kolmogorov Smirnov 2 Independent Samples with SPSSversion 20.00. Based on this result, guidance and counseling techers are suggested to do theinformation service planned by using the game to improve student self regulated learning.Keywords: Self regulated learning, Information Services